(untitled) (International Journal of Engineering and Computer Science, 2015)
In Present days WiFi provide easy access to internet through portable devices such as smartphones, tablets. This technique implement the current WiFi implementation in the way to design that allow mobile devices to advertise and discover small chunk of information in very energy efficient way. This is easily possible in the crowded environments. This mechanism is also known as energy efficient discovery in a WiFi network. Another way this is says implementation of current WiFi in driver level implementation.